Right ventricular diastolic function in aging: a head-to-head comparison between phase-contrast MRI and Doppler echocardiography - Kachenoura, Nadjia; Bollache, Emilie; Soulat, Gilles; Clément-Guinaudeau, Stéphanie; Ashrafpoor, Golmehr; Perdrix, Ludivine; Diebold, Benoit; Ladouceur, Magalie; Mousseaux, Elie (International Journal of Cardiovascular Imaging, 2021)
To evaluate right ventricle (RV) diastolic function from phase-contrast MRI (PC-MRI) in aging. 89 healthy individuals (50 men, 43 ± 15 years) underwent cardiac MRI including 2D PC-MRI (1.5T) and reference Doppler echocardiography of both ventricles on the same day. Conventional echocardiographic parameters were estimated: early (E, cm/s) and atrial (A) peak velocities as well as myocardial early peak longitudinal velocity (E′). PC-MRI images were analyzed using custom software, providing: E′, E and A waves along with respective peak flow rates (Ef, Af, mL/s) and filling volume (mL), for both ventricles. Intra- and inter-observer reproducibility was studied in 30 subjects and coefficients of variation (CoV) as well as intra-class correlation coefficients (ICC) were provided. RV diastolic function indices derived from PC-MRI data were reproducible (CoV ≤ 21%, ICC ≥ 0.75) and reliable as reflected by significant associations with left ventricular diastolic function indices assessed using both echocardiography (linear regression Pearson correlation coefficient r ≤ 0.59) and PC-MRI (r ≤ 71). Despite the fair associations between RV echocardiography and PC-MRI (r ≤ 0.25), the highest correlation with age was obtained for MRI Ef/Af ratio (r = − 0.64, p < 0.0001 vs. r = − 0.40, p = 0.0001 for echocardiographic E/A). Among PC-MRI E/A ratios, highest correlations with age were observed for flow rate and mean velocity ratios (r = − 0.61, p < 0.0001) as compared to maximal velocity ratios (r = − 0.56, p < 0.0001). Associations with age for E′ were equivalent between PC-MRI (mean velocity: r = − 0.40, p < 0.0001; maximal velocity: r = − 0.36, p = 0.0005) and echocardiography (r = − 0.36, p = 0.0006). Finally, the significant and age-independent associations between RV mass/end-diastolic volume and E′ were stronger for PC-MRI (mean velocity: r = − 0.36, p = 0.0006; maximal velocity: r = − 0.28, p = 0.007) than echocardiography (r = − 0.09, p = 0.38). PC-MRI tricuspid inflow and annulus myocardial velocity parameters were reproducible and able to characterize age-related variations in RV diastolic function.